BOOK REVIEW OF POWER IN ORGANIZATIONS BY JEFFREY PFEFFER - Nur Hasanah (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This book initiated â€œnew waveâ€ organizational studies that begin to edit, prune, apply, and synthesize what we have to see what we do not have yet, what we have too much of, and what we agree on as the basics. What makes this assessment plausible is the fact that Pfeffer has shown that the several perspectives now dotting the field can converge more strongly on a problem than mere lists of properties can. Pfeffer applies multiple perspectives simultaneously to a durable puzzle in organizations and shows not only that power is less puzzling than we thought but also that all perspectives we are currently working with have something to say about how that puzzle can be untangled most meaningfully. In doing so, Pfeffer has made a major contribution in the form of an important book.